Fluidization and Spouting of Fine Particles: A Comparison - Pranati Sahoo; Abanti Sahoo (Advances in Materials Science and Engineering)
The fluidization characteristics of fine particles have been studied in both the fluidized bed and spouted bed. The effect of different system parameters (viz. static bed height, particle size, particle density and superficial velocity of the fluidizing medium, rotational speed of stirrer, and spout diameter) on the fluidization characteristics such as bed expansion/fluctuation ratios, bed pressure drop, minimum fluidizing/spouting velocity, and fluidization index of fine particles (around 60 micron particle size) have been analyzed. A stirrer/rod promoter has been used in the bed to improve the bed fluidity for fluidization process and spout diameter has been varied for spouted bed. Mathematical expressions for these bed dynamics have been developed on the basis of dimensionless analysis. Finally calculated values of these bed dynamics are compared with the experimentally observed values thereby indicating the successful applications of these developed correlations over a wide range of parameters.